The Effectiveness of Acceptance and Commitment Therapy on Emotion Regulation Difficulties and Zest for Life in Couples Seeking Divorce - Rezaei Khoramabadi , Masoumeh; Gholipor, Forozan; Gholampour , Leila; Dadashi Omali , Maryam; Siahbazi, Faezeh (Mental Health and Lifestyle Journal, 2024)
The aim of the present study was to determine the effectiveness of Acceptance and Commitment Therapy (ACT) on emotion regulation difficulties and zest for life in couples seeking divorce. The research method was quasi-experimental with a pretest-posttest design and a control group. The statistical population consisted of couples seeking divorce who referred to counseling centers in Tehran in 2023. A convenience sampling method was used, and the sample included 28 individuals (14 in the experimental group and 14 in the control group). Data collection instruments included the Difficulties in Emotion Regulation Questionnaire and the Zest for Life Questionnaire. The experimental group received ACT-based therapy in 90-minute weekly sessions for eight weeks, while the control group did not receive any specific intervention. After the intervention, both groups were re-evaluated. The findings indicated that the mean posttest scores for emotion regulation and zest for life in the experimental group were significantly different compared to the control group. Therefore, Acceptance and Commitment Therapy has a significant effect on emotion regulation difficulties and zest for life in couples seeking divorce.